Development of an intelligent enzyme indicator for dynamic monitoring of the shelf-life of food products. (August 2015) - Brizio, Ana Paula Dutra Resem; Prentice, Carlos
Abstract: This work describes the development of a new smart time–temperature indicator, whose operating principle is based on the reaction between starch and iodine and the subsequent acting of an amylase on this complex, causing discoloration at a rate dependent on time and temperature of the medium. Laboratory simulations, manufacturing plant tests, and points of sale evaluated various enzyme concentrations in the TTI prototypes. The results showed that the color response of the indicators was visually interpreted as adaptive to measurement using colorimeter. Due to the possibility of defining the shelf-life of TTIs by varying enzyme concentrations, the indicators can be easily adapted to control the temperature conditions in the production chain of many perishable foods in a cheap, easy and accurate form. Industrial relevance: Temperature control during the distribution and storage of perishable products is often flawed, with conditions other than those recommended by the manufacturer. The difficulty in knowing the temperature history to which a food has been exposed to makes it difficult to predict its true shelf-life. An innovative alternative to dynamically ensure the validity of food can be the use of a smart time–temperature indicator (TTI). However, the success of the industrial application of TTIs depends on the simplicity, cost and reliability during operation, characteristics that have not yet been jointly observed in the indicators available in the market. In this perspective, it is part of the development of this work, which aims to develop a new TTI that presents a favorable combination of efficiency, reliability and viability. Thus, the aim is to contribute to the commercial acceptance of the concepts of smart packaging and in the establishment of regulation standards of usage, providing benefits to the conservation of a wide variety of foods. Highlights: The indicator discoloration was visually interpretable and adaptable to measurement. The new indicator presented good reproducibility during the conditions studied. The new TTIs can be easily used to control the temperature conditions of foods. The new TTI indicated the temperature in a cheap, easy, and accurate. The TTI can be stored frozen for long periods of time.